PENGARUH KELENGKAPAN PRODUK, HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA CAFÉ BEKNA DI SITUBONDO - Ediyanto, Ediyanto; Vinatil Jannah, Siti Nurvikria; Rofiqo, Andini Dwi (Growth, 2025)
This study aims (1) to determine the effect of product completeness, price and service quality partially influence on consumer satisfaction (2) to determine the effect of product completeness, price and service quality simultaneously affect consumer satisfaction (3) to determine among product completeness, price and quality of service that has a dominant effect on customer satisfaction. The method used is qualitative. The result of this research is the equation of multiple linear regression Y = -2,237E-17 + 1,019X1 + 0,154X2 + 0,418X3 + e. Partial statistical test or t test shows that the product completeness variable (X1) is 0,180 <ttable 1.986 and the significant value is 0,841 > 0.05, meaning that the product completeness variable (X1) has no effect on customer satisfaction (Y). The value for the price variable (X2) of 0,541 <ttable 1.986 and the significant value of 0.585> 0.05, meaning that the price variable (X2) has no effect on customer satisfaction (Y). The value for service quality (X3) tcount 4,235 > ttable 1.986 and a significant value of 0.000 <0.05, meaning that the service quality variable (X3) influences customer satisfaction (Y). Simultaneous statistical tests or F tests show Fcount 6,021 > Ftable 2.71 where the significant value is 0.001 <0.05. The dominant influential variable in this study was service quality (X3) of 4,232